ANALISIS YURIDIS PELAKSANAAN KUASA MENJUAL DALAM PENYELESAIAN KREDIT MACET PADA PT. BANK MANDIRI (PERSERO) TBK CABANG PEMATANGSIANTAR - DONNA FEBRYNA SIDAURUK (PREMISE LAW JURNAL, 2016)
In a banking loan agreement a debtor is usually required to give collateral such as movable property or immovable property which, in this research, is immovable property (land and building) which is bound with hypothecation. The research used judicial normative and descriptive analytic The result of the research shows that the certificate of the power to sell in the loan Agreement in PT Bank Mandari (Persero) Tbk, Pematanngsiantar Branch, does not have any legal force and tends to be contrary to UUHT No. 4/1996 concerning the sale of collateral underhandedly. The process of nonperforming loan execution on collateral, based on the certificate of the power to sell of PT Bank Mandiri (Persero) Tbk, Pematangsiantar Branch, is by sending a warning (summons 1, 2, and 3) to debtors and visit debtors' homes in persuasive approach. However, when they fail, the last resort is by using the power of attorney to sell as the basis for selling the collateral underhandedly. Beside that, it is difficult to meet debtors and the buyers do not want to buy the collateral because it is still placed by the third party. Keywords: Power to Sell, Selling Collateral, Nonconforming of PT Bank Mandiri (Persero) Tbk, Pematangsiantar Branch